Eotaxin induces migration of RBL-2H3 mast cells via a Rac-ERK-dependent pathway - Woo, CH; Jeong, DT; Yoon, SB; Kim, KS; Chung, IY; Saeki, T; Kim, JH (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2002)
Eotaxin is a potent chemokine that acts via CC chemokine receptor 3 (CCR3) to induce chemotaxis, mainly on eosinophils. Here we show that eotaxin also induces chemotactic migration in rat basophilic leukemia (RBL-2H3) mast cells. This effect was dose-dependently inhibited by compound X, a selective CCR3 antagonist, indicating that, as in eosinophils, the effect was mediated by CCR3. Eotaxin-induced cell migration was completely blocked in RBL-RacN17 cells expressing a dominant negative Racl mutant, suggesting a crucial role for Racl in eotaxin signaling to chemotactic migration. ERK activation also proved essential for eotaxin signaling and it too was absent in RBL-RacN17 cells. Finally, we found that activation of Rac and ERK was correlated with eotaxin-induced actin reorganization known to be necessary for cell motility. It thus appears that Racl acts upstream of ERK to signal chemotaxis in these cells, and that a Rac-ERK-dependent cascade mediates the eotaxin-induced chemotactic motility of RBL-2H3 mast cells. (C) 2002 Elsevier Science (USA). All rights reserved.